Docência no ensino superior no ISCED-Cabinda (Angola): formação de professores - atuação práticas pedagógicas - Francisco Antonio Macongo Chocolate (2016)
This work looks for analyse the teaching practice conceptions of education course teachers of ISCED-Cabinda, Angola, searching in this way for, identify the principal indicators about the thematic. Framed on studies camp of teaching in higher school, we started from multiplies considerations references functions of universitary teacher, that envolves the teaching but, also, the searching and administration activities, as well as the subjectivity consideration of elements envolved in teaching-learning process. Throw this, we found as problem situation the following: From What theoretical knowledge the education course teachers of ISCED-Cabinda use in the organization and execution of the lective activities in the classroom for the teachers formation in higher level?Due to this questioning, we derived an hipotetical formulation descriminated in: There is a knowledge transmissors positioning overlooking the studens subjectivity in teaching-learning process. The research had as theoretical line the historical-cultural approach of Vygotsky and colaborators and is characterized as qualitative research emphasized on case study. To collect the data we elect two instruments: semi-structured interview with the education course teachers of ISCED-Cabinda, four in the case and the discussing group with the same course students, five in the case. Throw this was elaborated a semi-structured interview script and for the discussing group, that incided on fundamental themes namely in the teachers and students characterization, surveying their formative course, on the universitaries´ teachers functions, on the conceptions, the intention and universitary teaching practice. Based on contents analysis of the information achieved were identified a combination of subcategory and of indicators that shows a mixture of conceptions of the teaching practice that is characterized as "knowledge transmissors" and practice "contextualizated". The consideration contextualizated, indicates, that the teachers started worrying about about developing actions that goes further the technical dimension, establishing also of the knowledge and pratical contents contextualized, appreciating the respect and the affective relationship between the teachers and students. the Characteristic practice of this model were determinant for the observance of a new model, it means, a new vision model of the teachers practice emergence.